Relationship between Reproductive Health Knowledge and Early Marriage Pregnancy in Adolescent Girls: A Study in Kepung, Kediri District - Mayrza Setiawan Putra; Adysta Tantiana Ayu P (Green Publisher Indonesia, 2024)
Adolescent girls who marry at a young age are vulnerable to reproductive health risks, especially premarital pregnancy, which can have serious impacts on their future. The high prevalence of premarital pregnancy among young married teenagers is a serious concern in the context of public health, especially in rural areas such as Kepung District, Kediri Re-gency. This study aims to determine the relationship between reproductive health knowledge among young married women and the incidence of premarital pregnancy in the area. The research method used is descriptive quantitative with an analytical design and cross-sectional approach. The research population was 58 young married women in Ke-pung District, Kediri Regency, while the sample consisted of 49 respondents who met the inclusion criteria. Data collection was carried out using a questionnaire, and data analysis included univariate and bivariate analysis using the chi-square test. Research findings show that there is a significant relationship between the level of reproductive health knowledge among young married women and the incidence of premarital pregnancy in Kepung District, Kediri Regency.